Karakteristik Morfologi Daun Tumbuhan Obat Tradisional Masyarakat Desa Darek sebagai Referensi dalam Praktikum Morfologi Tumbuhan - Wina Wafia Anggraini; Baiq Muli Harisanti; Septiana Dwi Utami (Biocaster : Jurnal Kajian Biologi, 2026)
Medicinal plants have long been utilized by the traditional community in Darek Village to treat various illnesses. One of the plant parts most commonly used for medicinal purposes is the leaf. Leaves exhibit diverse characteristics in terms of shape and size across different species. Leaf morphology includes features such as shape, color, size, venation pattern, leaf margin, leaf apex, leaf base, surface texture, and others. This study aims to identify the plant species whose leaves are used in traditional medicine by the Darek community and to describe the morphological characteristics of these medicinal leaves. This research employed a eksplorative descriptive approach using semi-structured interviews to document local knowledge regarding the use of medicinal plant leaves in Darek Village. Respondents were selected through a purposive sampling technique, involving community leaders and individuals recognized for their traditional knowledge of medicinal plants. The collected data were analyzed through data reduction, classification, and conclusion drawing to identify the plant species used medicinally and their leaf morphological traits. The findings indicate that the community utilizes 15 types of leaves from 13 plant families as traditional medicinal resources. In general, these medicinal plants display diverse leaf morphological characteristics, particularly in surface texture, venation type, and the shapes of the leaf margin, apex, and base. This morphological variation reflects the diversity of species employed and serves as a basis for the community to recognize and differentiate medicinal leaves. These findings highlight the richness of local knowledge, which holds potential for further development in ethnobotanical studies and the conservation of biological resources.